TGF-β Enhances Immunosuppression of Myeloid-Derived Suppressor Cells to Induce Transplant Immune Tolerance Through Affecting Arg-1 Expression - Cao, Peng; Sun, Zejia; Zhang, Feilong; Zhang, Jiandong; Zheng, Xiang; Yu, Baozhong; Zhao, Yong; Wang, Wei; Wang, Wei (Frontiers in Immunology, 2022)
Myeloid-derived suppressor cells (MDSCs) are a class of heterogeneous myeloid cells, which play an important role in immunosuppression. We intended to find an effective method that can produce MDSCs with significantly better efficiency and promote immune tolerance for transplant rejection through cell therapy. It has been reported that granulocyte and macrophage colony stimulating factor (GM-CSF) could induce MDSCs in vitro to cause immunosuppression. In the present study, transforming growth factor β (TGF-β) was added to the induction system and flow cytometry analysis was used to detect the phenotypes of induced MDSCs. Their potential immunosuppressive function and mechanisms were determined by co-culturing MDSCs with stimulated T cells in vitro and transferring MDSCs to the skin grafted C57BL/6J mouse models in vivo. It was found that addition of TGF-β could effectively cause bone marrow cells to differentiate into a group of cells with stronger immunosuppressive functions thereby inhibiting the proliferation of stimulated T cells. The population of CD11b+Gr-1+ MDSCs also increased significantly as compared with GM-CSF alone treatment. While detecting for immunosuppressive effectors, we found that expression of arginase 1 (Arg-1) was significantly upregulated in these MDSCs, and inhibitor of Arg-1 significantly suppressed their immunosuppressive capabilities. Moreover, an adoptive transfer of these cells significantly prolonged survival of allo-skin and improved immune tolerance in vivo. These findings indicated that TGF-β + GM-CSF could serve as an effective and feasible method to induce powerful immunosuppressive MDSCs in vitro. Thus, TGF-β + GM-CSF-induced MDSCs may have a promising role in prevention of the graft rejection.